Toward blockchain technology in the energy environment - Baashar Y.; Alkawsi G.; Alkahtani A.A.; Hashim W.; Razali R.A.; Tiong S.K. (MDPI AG, 2023)
accountability; detection method; electricity generation; electricity industry; energy management; energy storage